Posttranslational Protein Modifications in Type 1 Diabetes - Genetic Studies with PCMT1, the Repair Enzyme Protein Isoaspartate Methyltransferase (PIMT) Encoding Gene (The Review of Diabetic Studies, 2023)
BACKGROUND: Posttranslational protein modifications have been implicated in the development of autoimmunity. Protein L-isoaspartate (D-aspartate) O-methyltransferase (PIMT) repairs modified proteins and is encoded by PCMT1, located in a region linked to type 1 diabetes (T1D), namely IDDM5. AIM: To evaluate the association between genetic variations in the PCMT1 gene and T1D. METHODS: Firstly, PCMT1 was sequenced in 26 patients with T1D (linked to IDDM5) and 10 control subjects. The variations found in PCMT1 were then tested (alone and interacting with a functional polymorphism in SUMO4 and with HLA) for association with T1D in 253 families (using transmission disequilibrium test). In a third step, the association of the functional variation in PCMT1 (rs4816) with T1D was analyzed in 778 T1D patients and 749 controls (using chi-square test). In vitro promoter activity was assessed by transfecting INS-1E cells with PCMT1 promoter constructs and a reporter gene, with or without cytokine stimulation. RESULTS: Four polymorphisms in complete linkage disequilibrium were identified in PCMT1 (5’ to the gene (rs11155676), exon 5 (rs4816) and exon 8 (rs7818 and rs4552)). In the whole cohort of 253 families, the allele associated with increased PIMT enzyme activity (rs4816, allele A) was less frequently transmitted to the affected than to the non-affected offspring (46% vs. 53%, p = 0.099). This finding was even more evident in the subset of families where the proband had high-risk SUMO4 (p = 0.069) or low-risk HLA (p = 0.086). Surprisingly, in the case-control study with 778 cases and 749 controls, an inverse trend was found (40.36% of patients and 36.98% of controls had the allele, p = 0.055). PCMT1 promoter activity increased with cytokine stimulation, but no differences were detected between the constructs adjacent to rs11155676. CONCLUSION: PCMT1 was virtually associated with T1D in groups defined by other risk genes (SUMO4 and HLA). A general association in a not further defined sample of T1D patients was not evident. Verification in a larger population is needed.